DEVELOPMENT OF MULTI-CHANNEL POTENTIOSTAT ELECTROCHEMICAL BIOSENSOR READER DEVICE - Fawwaz Ramadhan, Iqbal
Along with the development of technology in the biomolecular field, there are many methods that aim to consider measurement variations including electrochemical biosensor measurements. The biosensor itself was chosen because it is considered to have several advantages that are able to detect various types of analytes, speed up the measurement duration and are relatively inexpensive instruments. This is what makes biosensors widely used, especially in the health sector. In general, electrochemical-based analyzers are often chosen because of their simplicity, durability, and advantages as well as their minimal maintenance. One tool that is quite important in measuring electrochemical-based biosensors is a potentiostat which is a tool that functions to assist biosensors. However, there are obstacles in the procurement of potentiostat, causing the need for potentiostat fabrication that focuses on low prices so that it can be reached by small and medium-sized units in order to develop a multifunctional mini laboratory and its supporting activities. Given the minimal space required the development of small and portable instruments may be needed to reach more adopters of the technology. In this research, we created a potentiostat system (ESPotensio) based on the ESP32 microcontroller for signal acquisition, processing, and data communication. Various measurement methods are implemented not only limited to Cyclic Voltammetry but also other methods, such as Linear Sweep Voltammetry, analysis using several Pulse Voltammetry methods, and observation of current activity against time with Chronoamperometry. Applying various measurement methods aims to make this potentiostat more functional and reliable in some special cases where this method is required. In addition, measurements can also be carried out simultaneously in semi-parallel for three analytes simultaneously with three measurement channels. The test results show that this tool can produce voltammograms with an average accuracy of more than 80% for each method when compared to Emstat Pico, a commercial potentiostat, as a reference.